Identification of Novel Inhibitors of the Type I Interferon Induction Pathway Using Cell-Based High-Throughput Screening. (October 2016) - Gage, Zoe O.; Vasou, Andri; Gray, David W.; Randall, Richard E.; Adamson, Catherine S.
Production of type I interferon (IFN) is an essential component of the innate immune response against invading pathogens. However, its production must be tightly regulated to avoid harmful effects. Compounds that modulate the IFN response are potentially valuable for a variety of applications due to IFN's beneficial and detrimental roles. We developed and executed a cell-based high-throughput screen (HTS) targeting components that participate in and/or regulate the IRF3 and nuclear factor (NF)–κB branches of the IFN induction pathway. The assay detects activation of the IFN induction pathway via an enhanced green fluorescent protein (eGFP) reporter gene under the control of the IFNβ promoter and was optimized, miniaturized, and demonstrated suitable for HTS as robust Z′ factor scores of >0.6 were consistently achieved. A diversity screening set of 15, 667 small molecules was assayed and two novel hit compounds validated that specifically inhibit the IFN induction pathway. We demonstrate that one of these compounds acts at or upstream of IRF3 phosphorylation. A second cell-based assay to detect activation of the IFN signaling (Jak-Stat) pathway via an eGFP reporter gene under the control of an IFN-stimulated response element (ISRE) containing MxA promoter also performed well (robust Z′ factor >0.7) and may therefore be similarly used to identify small molecules that modulate the IFN signaling pathway.